2009
DOI: 10.1016/j.jmb.2009.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the Lipid-Binding and Stability Properties of the Central Rod Domain of Human Dystrophin

Abstract: Dystrophin is a cytoskeletal protein that confers resistance to the sarcolemma against the stress of contraction-relaxation cycles by interacting with cytoskeletal and membrane partners. Apart from several proteins, membrane phospholipids are a partner of the central rod domain made up of 24 spectrin-like repeats, separated into sub-domains by four hinges. We previously showed that repeats 1 to 3 bind to membrane anionic phospholipids, while repeats 20 to 24 are not able to do so. We focus here on the phosphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 63 publications
6
55
0
2
Order By: Relevance
“…However, the PorodDebye plots show a large plateau assessing the compactness of the protein fragments, to the relative exception of the R16-19 fragment that could be slightly more dynamic given the calculated Porod-Debye exponent (Table S2 and Figure S2B). These features are consistent with dystrophin fragments being folded proteins, and in agreement with circular dichroism observations (19). At the same time these results are compatible with the putative inter-repeat regions variability as previously described (23).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, the PorodDebye plots show a large plateau assessing the compactness of the protein fragments, to the relative exception of the R16-19 fragment that could be slightly more dynamic given the calculated Porod-Debye exponent (Table S2 and Figure S2B). These features are consistent with dystrophin fragments being folded proteins, and in agreement with circular dichroism observations (19). At the same time these results are compatible with the putative inter-repeat regions variability as previously described (23).…”
Section: Resultssupporting
confidence: 93%
“…We dissected dystrophin in eight native purified fragments of the central domain covering 23 over the 24 repeats of the whole central domain ( Figure 1A, Table S1). Proteins were obtained as pure ( Figure 1B) and α-helix folded molecules as previously observed (19,20). The Guinier approximation analysis of the SAXS curves indicated that the fragments were non-aggregated ( Figure S1).…”
Section: Resultsmentioning
confidence: 56%
“…Previous studies indicated that spectrinlike repeat 17 is localized to the second actin binding domain of dystrophin (Amann et al, 1999) and is also important for anchoring neuronal nitric oxide synthase (nNOS) to the sarcolemma (Lai et al, 2009). Moreover, both spectrin-like repeat 17 and 18 can bind anionic phospholipids (Legardinier et al, 2009). Thus, loss of spectrin-like repeats 17 and 18 might compromise interactions between dystrophin and actin filaments, nNOS, anionic phospholipids, or some combination of all three, and possibly explain the underlying defect in this particular subset of QM patients.…”
Section: Introductionmentioning
confidence: 99%
“…Leur connaissance est essentielle pour élucider la fonctionnalité de la dystrophine normale et de ses variants pathologiques. Le domaine central en particulier possède de multiples interactions avec les lipides membranaires qui maintiennent la dystrophine en contact avec le sarcolemme [17,18], l'actine [2], la sérine/thréonine kinase Par-1b [39], les filaments intermédiaires de type synémines α et β [4], les microtubules [29] et une protéine enzymatique jouant un rôle clé dans l'activité musculaire, l'oxyde nitrique synthase neuronale ou nNOS [15,20]. Les premières mutations du gène DMD ont été identifiées il y a 30 ans.…”
Section: Rabah Ben Yaou Aurélie Nicolas France Leturcq éLisabeth Lunclassified
“…La dystrophine est composée de quatre grands domaines [14,16] (Figure 1 [17,18], l'actine (domaine ABD2, répétitions 11-17) [2], la sérine/thréonine kinase Par-1b (répétitions R8-R9) [39], les synémines α et β qui sont des protéines de la famille des filaments intermédiaires (répétitions R11-R14) [4] et l'oxyde nitrique synthétase neuronale ou nNOS (répétitions R16-R17) [15,20] et enfin les microtubules (répétitions R20-24) [29] permettant de maintenir près du sarcolemme cette protéine enzymatique jouant un rôle clé dans l'activité musculaire.…”
Section: Rabah Ben Yaou Aurélie Nicolas France Leturcq éLisabeth Lunclassified